Synthesis and study of antimicrobial activity of some tetrahydrocarbazole derivatives substituted with NSAID - Mustafa H. Mahdi; Ashour H. Dawood; Dhurgham Q. Shaheed (College of Pharmacy / Mustansiriyah University, 2022)
New tetrahydrocarbazole derivatives substituted at the heteroatom (N) by non-steroidal anti-inflammatory drug (NSAIDs) were synthesized by reaction of cyclohehexanon (C.H.N.) with phenyl hydrazine (P.H.Z.) to form tetrahydrocarbazole (THCZ), where the latter is reacted with NSAID (Ketoprofen) via amide bond to yield substituted THCZ, compounds chemical structures were verified by: 1H, 13C NMR and FTIR spectroscopy. Antifungal activity of the synthesized compounds was investigated by docking study and in vitro test to reveal good antifungal activity, but the in vitro test also showed that the compounds have weak to moderate antibacterial activity.